Justice: a reader - Sandel, Michael J. (Oxford University Press, 2007)
Introduction : doing the right thing -- Utilitarianism -- Libertarianism -- Locke : property rights -- Markets and morals : surrogate motherhood, military service -- Kant : freedom as autonomy -- Rawls : justice as fairness -- Distributive justice : equality, entitlement, and merit -- Affirmative action : reverse discrimination? -- Aristotle : justice and virtue -- Ability, disability, and discrimination : cheerleaders and golf carts -- Justice, community, and membership -- Moral argument and liberal toleration -- Morality and law : same-sex marriage, for and against